KESESUAIAN PERLAKUAN AKUNTANSI MURABAHAH DENGAN PSAK SYARIAH N0.102 PADA ISLAMIC MICROFINANCE INTITUTIONS - Latifah, Eny (Al-Musthofa: Journal of Sharia Economics, 2022)
The purpose of this study was to determine the appropriateness of the accountingtreatment of murabahah financing in Islamic Microfinance Institutions named KSPPSBMT Mandiri Sejahtera East Java as a seller and buyer with PSAK Syariah No. 102.This study uses descriptive qualitative research by combining analyzed research instruments asdata triangulation to make it easier to match concepts and theories to the practice containedin the research object so that it is easier to get results that are in accordance with the facts.The results showed that the accounting treatment of murabahah financing at KSPPS BMTMandiri Sejahtera East Java was mostly carried out in accordance with PSAK Syariah No.102, both in terms of recognition of acquisitions, recognition of profits. However, therecognition and measurement of urbun (advance payment) is not appropriate because when thefinished goods are purchased by members, urbun is not recognized as a receivable but as anadvance for the remaining acquisition of goods for murabahah financing.Keywords: Murabahah Accounting, PSAK Syariah No. 102. and Islamic MicrofinanceInstitutions